Serum malondialdehyde and adiponectin in albuminuric kidney disease patients - Ali, Syed Liaquat; Panhwar, Ghazala; Zafar, Shahid; Ali, Syed Naqeeb; Khoso, Mohammad Yousuf; Khanam, Aziza; Naseer, Momina (International Journal of Research in Medical Sciences, 2019)
Background: Diabetes, hypertension, oxidative stress, obesity, adipocytokine dysfunction, and dyslipidemia are causative factors in development of Chronic Kidney Disease (CKD). Adiponectin secreted from adipose tissue, has Reno protective effect against development of albuminuria in animal studies. The previous studies investigated the relationship between serum adiponectin level and urinary albuminuria in kidney disease patients, but the results are conflicting. Methods: The pre diagnosed kidney disease patients were divided into microalbuminuria and macroalbuminuria groups, while control subjects were called as normoal buminuria group. The pre diagnosed adult kidney disease patients of both genders with age matching control subjects with no known comorbidity were included in the study. Whereas pregnant female patients and the patients with comorbidity were excluded from the study. The demographic data and the anthropometric data of control and kidney patients were recorded. The blood was analyzed for Glycosylated Hemoglobin (HbA1c), electrolytes, glucose, calcium, total protein, albumin, urea, creatinine adiponectin and malondialdehyde. The Urine was analyzed for Creatinine and albuminuria. The glomerular filtration rate was estimated. Results: The blood pressure, blood urea, creatinine, glycated hemoglobin, malondialdehyde, adiponectin levels were higher in albuminuric kidney patients as compared to normal control subjects. The mean glomerular filtration rate was lowest in macroalbuminuric patients as compared to micro and normoalbuminuric patients. The serum adiponectin and serum malondialdehyde both showed positive correlation with serum creatinine, and with albuminuria/urinary creatinine ratio. Conclusions: The study concludes that, positive correlation of serum malondialdehyde with adiponectin and albuminuria.